Making Mental Health : A Critical History / Elizabeth Roberts-Pedersen. - Roberts-Pedersen, Elizabeth (Routledge, 2024)
The book historicizes mental health by examining the concept from the 'madness' of the late 19th century to the changing ideas about its contemporary concerns and status.